Greenspace and Crime: An Analysis of Greenspace Types, Neighboring Composition, and the Temporal Dimensions of Crime. (May 2017) - Kimpton, Anthony; Corcoran, Jonathan; Wickes, Rebecca
Objectives: There is a growing interest in the relationship between greenspace and crime, yet how particular greenspace types encourage or inhibit the timing and types of greenspace crime remains largely unexplored. Drawing upon recent advances in environmental criminology, we introduce an integrated suite of methods to examine the spatial, temporal, and neighborhood dynamics of greenspace crime. Methods: We collate administrative, census, and crime incident data and employ cluster analysis, circular statistics, and negative binomial regression to examine violent, public nuisance, property, and drug crimes within 4, 265 greenspaces across Brisbane, Australia. Results: We find that greenspace amenities, neighborhood social composition, and the presence of proximate crime generators influence the frequency and timing of greenspace crime. Conclusions: Our analyses reveal that particular types of greenspaces are more crime prone than others. We argue that this is largely due to the presence of amenities within greenspaces allied with the sociodemographic context of surrounding neighborhoods. We conclude that understanding how these factors influence the behaviors of potential offenders, victims, and guardians is necessary to better understand the spatial distribution of greenspace crime and provide an evidence base for crime prevention initiatives.